(untitled) - Wilson, Richard W. (Cambridge, 1970)
Attempts to explain the often puzzling behavior of the Chinese in terms of the concept of "face" and how Chinese children acquire attitudes toward authority, group cohesiveness, acceptable targets for aggression, and other nonpolitical but relevant aspects of personality. Data from 3 large primary schools are presented, and the relationships of "face" to group loyalty, political hierarchies, and political stability and how this relationship affects the style of government in China are discussed...
Keywords: Education, Elementary,Giáo dục, Tiểu học,Political socialization,Xã hội hóa chính trị; Đài Loan; Taiwan